Ethiopia's Potato Seed System: Regulatory Challenges, Quality Assurance Issues, and Pathways for Improvement ─ A mini review [version 1; peer review: 2 approved] - Ebrahim Seid; Lemma Tessema (F1000Research)
Background Ethiopia’s potato seed system is currently hindered by a disjointed regulatory framework, insufficient quality assurance processes, and a lack of collaboration among stakeholders, which collectively impede agricultural productivity and food security. The regulatory environment is characterized by inconsistent seed certification practices and a dependence on informal seed sources, negatively affecting the quality of potato seeds available to farmers. Although potatoes play a crucial role in global food security by providing high yields compared to other staple crops, the sector grapples with significant challenges due to bureaucratic inefficiencies, limited technical expertise, and the widespread presence of counterfeit seeds throughout the value chain. Methods To tackle these challenges, this mini-review outlines potential improvements, stressing the necessity for a unified regulatory framework tailored to the unique issues of vegetatively propagated crops. For this reason, we have used different literature source from web of science, Pubmed, Google Scholar, ResearchGate and other scientific websites. We have documented the most relevant information focusing on potato seed system, regulatory frameworks, quality assurance bottlenecks and pathways for improvement across the seed value chain. Results our paper highlights key recommendations that includes enhancing training for regulatory staff, investing in research for disease-resistant varieties, and bolstering public-private partnerships to encourage innovation and resource sharing. Furthermore, improving traceability in the seed supply chain is essential for maintaining seed quality and integrity. Conclusions This review calls for a comprehensive strategy that fosters stakeholder engagement and promotes sustainable practices to rejuvenate Ethiopia’s potato seed system, thereby supporting the livelihoods of millions of smallholder farmers and strengthening national food security through integrated seed sector development and capacity improvement of the seed regulatory body as well as smallholder farmers.